Study on Heritage Value and Composition of Changqu Water Conservancy Project. (January 2019) - Jun, Deng; Yunpeng, Li; Jiangang, Liu; Bo, Zhou; Jianzhong, Xu; Yugao, Wei
Abstract: Changqu, located in Xiangyang City, northwest of Hebei Province and in the middle reaches of Manhe River Basin of Hanjiang River, tributary of the Yangtze River, is a "Joining reservoirs" type water storage and diversion irrigation project with a long history of more than 1200 years. Based on the origin, evolution and management research of Changqu, this paper puts forward the composition of Changqu water conservancy heritage and analyzes its value.